Progressive Legal Approaches of the Constitutional Justice Reasoning on Judicial Review Cases: Challenges or Opportunities? - Wijayanti, Septi Nur; ALW, Lita Tyesta; Lailam, Tanto; Iswandi, Kelik (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The Constitutional Court often uses a positive legal approach, and some of the decisions it produces do not contain substantive justice. In its development, the Constitutional Court began to face a new paradigm as an institution for interpreting the constitution and began to use a progressive legal approach. This study aims to examine the application of a positivist legal approach and the urgency of using the progressive legal approach in the law review process. This research is normative legal research. Based on the results of this research, the Indonesian legal system is designed to accommodate human interests and needs through progressive legislation. The Constitutional Court, through a progressive legal approach, can issue decisions that fulfill substantive justice. This research is used in several cases, such as the heart article decision, ultra petite, and open legal policy. It can be concluded that through a progressive legal approach, it is a challenge for judges to guard the constitution through judicial review and an opportunity to prove that the Constitutional Court is an institution that prioritizes the constitutional rights of the people. In addition, the Constitutional Court can restore its spirit as the guardian of the constitution and democracy.